Assessing Emissions of Volatile Organic Componds from Landfills Gas - Fahime Khademi; Mohammad Reza Samaei; Kourosh Azizi; Abbas Shahsavani; Hassan Hashemi; Aida Iraji; Abdolkhalegh Miri (Shiraz University of Medical Sciences, 2016)
Background: Biogas is obtained by anaerobic decomposition of organic wastes buried materials used to produce electricity, heat and biofuels. Biogas is at the second place for power generation after hydropower and in 2000 about 6% of the world power generation was allocated to biogas. Biogas is composed of 40-45 vol% CO2, 55-65 vol% CH4, and about 1% non-methaneVOCs, and non-methane volatile organic compounds. Emission rates are used to evaluate the compliance with landfill gas emission regulations by the United States Environmental Protection Agency (USEPA). BTEX comounds affect the air quality and may be harmful to human health. Benzene, toluene, ethylbenzene and xylene isomers that are generally called BTEX compounds are the most abundant VOCs in biogas. Methods: Sampling of VOCs in biogas vents was operated passively or with Tedlar bags. 20 samples were collected from 40 wells of old and new biogas sites of Shiraz' landfill. Immediately after sampling, the samples were transferred to the laboratory. Analysis of the samples was performed with GC-MS. Results: The results showed that in the collection of the old and new biogas sites, the highest concentration of VOCs was observed in toluene (0.85ppm) followed by benzene (0.81ppm), ethylbenzene (0.13ppm) and xylene (0.08ppm). Conclusion: The results of the study showed that in all samples, most available compounds in biogas vents were aromatic hydrocarbon compounds.These compounds' constituents originate from household hazardous waste materials deposited in the landfill or from biological/chemical decomposition processes within the landfill.